A new species of Malacophagomyia (Malacophagomyia) Lopes, 1966 (Diptera: Sarcophagidae) collected from an urban zone of Southern Colombia - Córdoba-Suarez, Eric; Ramos-Pastrana, Yardany; Mulieri, Pablo Ricardo (Zootaxa, 2024)
Malacophagomyia Lopes, 1966 is a genus with Neotropical distribution, composed of two subgenera and four species. A new species of Malacophagomyia is described from Colombia, Malacophagomyia (Malacophagomyia) gaelana sp. nov. (type-locality: Caquetá, Florencia), collected in the urban area. Key to species identification and a distribution map for the species of the genus is presented.